In control or out of control?: Worker perceptions of autonomy and control using self-reliant digital systems at airports. (7th April 2023) - Bardmann, Mona-Maria; Ruiner, Caroline; Künzel, Laura; Klumpp, Matthias
Abstract : Self-reliant digital systems (SDS) can adapt to changing circumstances and environments, evaluate complex situations, make decisions and optimise processes. In this context, work processes also change, since SDS are controlled by workers but are also partly out of control, that is, processing information independently and without worker influence. It can be expected that handling and interacting with SDS impact workers' perception of autonomy and control and their interrelationship. This paper focuses on these developments at airports and is based on 24 interviews with airport and flight staff. The findings point to a difference between objective control and the perception of control. Moreover, we identify autonomy-enhancing and autonomy-restricting forms of control in contexts using SDS. In this sense, the article contributes to clarifying autonomy and control in the specific context of SDS at airports and conceptualising the interrelation of autonomy and control.